Stress distribution on denture-bearing areas with various thickness of soft denture liner using finite element analysis - Andreas; Ariyani; Ismet Danial (Indonesia Prosthodontic Association, 2023)
Background: Denture-bearing areas in edentulism are unable to tolerate masticatory load because of severe alveolar ridge resorption, which decreases masticatory function in the stomatognathic system. Due to the cushioning effect, the use of soft denture liner (SDL) helps reduce the masticatory load placed upon the denture-bearing areas. The physical properties and thickness of SDL have an impact on the stress distribution and cushioning effect. The masticatory load will harm the alveolar ridge and lead to more severe resorption, when modulus elasticity of SDL lower than the mucosa. The stress distribution of the masticatory load can be analyzed more accurately in-silico study using Finite Element Analysis (FEA) method. Objectives: In this paper, the stress distribution in denture-supporting areas with various SDL thicknesses is evaluated using FEA. The thickness of SDL contributes to the distribution of stress upon the denture-bearing areas by minimizing the masticatory load. Conclusion: Through the same modulus elasticity of the mucosa and SDL is able to equally distribute stress on the denture-bearing areas. Keywords: stress distribution, denture-bearing area, soft denture liner thickness, finite element analysis